CLINICAL AND RADIOLOGICAL PARAMETERS IN MALIGNANT SPINAL TUMORS: A DESCRIPTIVE ANALYSIS - Marcelo Diniz de Menezes; Mariana Demétrio de Sousa Pontes; Carlos Fernando Pereira da Silva Herrero (Acta Ortopédica Brasileira)
Abstract Objective: To describe the clinical and radiological parameters of spine malignant tumors. Methods: This is a therapeutic study of the descriptive retrospective type. Clinical evaluation included age, sex, tumor lesions, treatments, surgical procedures, and complications. The radiological evaluation analyzed radiographic exams, computed tomographies, and MRIs, focusing on morpho-pathological characteristics and the treatments employed. Results: Among the 236 patients evaluated, the majority were female, aged 6 to 91 years. The main complaint reported was low back pain. The most commonly used surgical approach was the posterior access, including pedicle fixation and decompression of the spinal canal. The most prevalent complication observed was infection. The majority of patients had primary breast tumors. The predominantly affected segment of the spine was the thoracic. Upon analyzing the portions of the spine affected, it was observed that the posterior arch portion was the most commonly affected. Conclusion: The clinical and radiological presentation of patients with metastatic lesions in the spine in our sample was similar to reports in the literature. Surgical outcomes aligned with previous expectations. Initial symptoms were noted, varying intervals between symptoms, diagnosis, and treatment. Level of Evidence III; Comparative Retrospective Study.